2012
DOI: 10.1016/j.jcf.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Reduced levels of active GLP-1 in patients with cystic fibrosis with and without diabetes mellitus

Abstract: Glucagon like peptide 1 (GLP-1) is an incretin hormone released as a bioactive peptide from intestinal L-cells in response to eating. It acts on target cells and exerts several functions as stimulating insulin and inhibiting glucagon. It is quickly deactivated by the serine protease dipeptidyl peptidase IV (DPP-IV) as an important regulatory mechanism. GLP-1 analogues are used as antidiabetic drugs in patients with type 2 diabetes. We served patients with cystic fibrosis (CF, n=29), cystic fibrosis related dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 49 publications
3
28
0
7
Order By: Relevance
“…Park et al (2007) treated 8-week-old male db/db mice with the long-acting GLP-1R agonist liraglutide for 8 weeks and found that the expression of transforming growth factor-β1 and type IV collagen were significantly decreased. Hillman et al (2012) recently found that GLP-1 levels were significantly reduced in cystic fibrosis patients (P < 0.01) compared with healthy individuals. In an electron microscope study, Tang et al (2008) observed that the endothelial basement membrane thickness of pulmonary capillaries was significantly decreased following treatment with GLP-1 for 8 weeks in the Otsuka-Long-Evans-Tokushima fatty rat model (P < 0.01).…”
Section: Discussionmentioning
confidence: 96%
“…Park et al (2007) treated 8-week-old male db/db mice with the long-acting GLP-1R agonist liraglutide for 8 weeks and found that the expression of transforming growth factor-β1 and type IV collagen were significantly decreased. Hillman et al (2012) recently found that GLP-1 levels were significantly reduced in cystic fibrosis patients (P < 0.01) compared with healthy individuals. In an electron microscope study, Tang et al (2008) observed that the endothelial basement membrane thickness of pulmonary capillaries was significantly decreased following treatment with GLP-1 for 8 weeks in the Otsuka-Long-Evans-Tokushima fatty rat model (P < 0.01).…”
Section: Discussionmentioning
confidence: 96%
“…Toplumda T2DM gelişmesine yol açan bazı genetik varyasyonların ve gen polimorfizmlerin KFİDM gelişmesinde de rol oynayabileceği ve hastalığın daha erken yaşlarda görülmesine yol açabileceği belirtilmiştir (15,16). KFİDM gelişmesinde inkretin hormonlarının rolünün ne olduğu konusunda ise daha fazla çalışmaya ihtiyaç vardır (17,18). Sinsi bir klinik seyre sahip olan KFİDM'un bulguları klasik diyabet belirtileri (poliüri, polidipsi, kilo kaybı), boy uzama hızında yavaşlama, pulmoner fonksiyonlarda açıklanamayan azalma ve protein Yılmaz ve ek olarak multivitamin desteği içeren diyet uygulanmalıdır.…”
Section: Discussionunclassified
“…Patients with CF have also been shown to have decreased GLP-1 activity compared to normal controls, which may contribute to glucose abnormalities [9]. CF is a complex multisystem disease, and multiple defects in nutritional status and metabolism also contribute to observed glucose abnormalities.…”
Section: Pathophysiologymentioning
confidence: 99%